2003
DOI: 10.1097/00000542-200305000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Morphine with Ketamine for Patient-controlled Analgesia

Abstract: Using a novel method to analyze drug combinations, the study supports combinations of morphine with ketamine in a ratio of 1:1 and a lockout interval of 8 min for postoperative PCA following spine and hip surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 1 publication
2
35
0
3
Order By: Relevance
“…A qualitative review of randomized trials concluded that, for thoracic surgery, adding ketamine to opioid for i.v PCA was superior to i.v PCA opioid alone, but the benefit of this addition remained unclear for abdominal surgery [16]. A 1:1 ratio with a lockout interval of 8 min, such as the one used in this case, has been described with positive effects after major orthopaedic procedures [20].…”
Section: Pca Of Morphine With Ketaminementioning
confidence: 90%
“…A qualitative review of randomized trials concluded that, for thoracic surgery, adding ketamine to opioid for i.v PCA was superior to i.v PCA opioid alone, but the benefit of this addition remained unclear for abdominal surgery [16]. A 1:1 ratio with a lockout interval of 8 min, such as the one used in this case, has been described with positive effects after major orthopaedic procedures [20].…”
Section: Pca Of Morphine With Ketaminementioning
confidence: 90%
“…PCA without background infusion is also used. Post-operative PCA usage has been described for analgesics such as morphine, piritramide, fantanyl, tramadol, and others [47][48][49][50][51]. In a systematic review, Walder and colleagues showed that the some evidence exists that in the postoperative pain setting, PCA with opioids, compared with conventional opioid treatment, improves analgesia and decreases the risk of pulmonary complications, and that patients prefer this option [52].…”
Section: Examples Of Closed-loop Drug Administrationmentioning
confidence: 99%
“…Vários trabalhos mostraram que a cetamina em baixas doses foi segura, sendo potente adjuvante dos opióides tanto na qualidade do alívio da dor quanto na redução da quantidade de opióide consumida no período pós-operatório 39,62,100,113,[118][119][120] . Após testar várias combinações de morfina e cetamina racêmica em analgesia controlada pelo paciente (ACP) venosa, um estudo verificou que a relação de 1:1 dessa solução promove melhor efeito analgésico e menos efeitos colaterais em pacientes submetidos a cirurgias espinhais ou de quadril 117 . Entretanto, outros estudos não conseguiram demonstrar esse benefício em outros tipos de procedimento cirúrgico [121][122][123] , com uso de R(-) cetamina 124 ou outras doses de cetamina racêmica utilizadas 112,114 .…”
Section: Estudos Clínicosunclassified
“…Contudo, a cetamina por essa via de administração, pode provocar importante reação inflamatória no local da injeção 104 . Por via venosa, a cetamina tem sido usada através de injeção única em bolus 37,105 , injeção em bolus seguida de infusão contínua 39,62,[106][107][108] , infusão contínua isolada ou associada a opióide ou benzodiazepínico 62,109-112 e por analgesia controlada pelo paciente (ACP) [113][114][115][116][117] . A eficácia analgésica da cetamina racêmica por via venosa depende da dose usada na infusão, da dose inicial e da associação a opióides.…”
unclassified